Fragility and conflict: Addressing crises and building resilient food systems - Abay, Kibrom A.; Ambler, Kate; Bloem, Jeffrey R.; Kosec, Katrina; Siddig, Khalid (International Food Policy Research Institute, 2025)
More than ever before, hunger and malnutrition are concentrated in fragile and conflict-affected areas around the world. This chapter reflects on the evolution of food policy research conducted in these areas over the past 50 years and looks ahead at how policy solutions will need to evolve to address the critical challenges that fragility and conflict present for building resilient food systems.